Sialadenoma papilliferum: clinicopathologic, Immunohistochemical, molecular analyses of new five cases and review of the literature - Shuai Chen; Jie Peng; Chuantao Yuan; Lin Sun; Renya Zhang; Yan Sun (Diagnostic Pathology, 2021)
Abstract Background Sialadenoma papilliferum (SP) is an extremely rare benign neoplasm of salivary glands. To explore and define the clinicopathological features of SP, we retrospectively analyzed 89 cases previously reported and five new cases. Methods The clinical features, histopathology, immunohistochemistry and molecular analysis of our cases were further performed and the related literatures were reviewed and analyzed. Results Combining 89 cases from the literature with our cases, the hard palate was the most common locations for SP. However, two of our cases were rarely located in the esophageal mucosa. Among all cases, the male gender was more affected, with the average age and median age of 61.8 and 62 years, respectively. Conventional histomorphologically, SP was characterized by complex papillary structures with a biphasic growth pattern of exophytic squamous component and endophytic glandular component. The glandular structures were lined by a double layer of epithelium composed of flattened or cuboidal basal cells and a cuboidal or columnar luminal cells formed papillary infoldings into the ductal lumina. Immunohistochemically, the luminal epithelial configurations showed strong expression of CK7 along the luminal cell membrane, while the basal myoepithelia displayed strong nuclear p63 expression. In both the glandular and squamous tumour components showed BRAF V600E-positive immunostaining and BRAF V600E mutation. Conclusion For the first time, we have comprehensively aggregated and analyzed 90 cases sialadenoma papilliferum from almost all previous publications, and further explored the clinicopathological features of SP; concordantly, this study demonstrated that SP shows a papillomatous growth pattern with exophytic and endophytic proliferation of ductal epithelium composed of double-layered cells harboring BRAF V600E mutation. Additionly, adequate treatment for SP is surgical excision, with a favorable prognosis in patients.